2015
DOI: 10.1016/j.jmb.2014.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Orientation of Myosin Binding Protein C in the Cardiac Muscle Sarcomere Determined by Domain-Specific Immuno-EM

Abstract: Myosin binding protein-C is a thick filament protein of vertebrate striated muscle. The cardiac isoform (cMyBP-C) is essential for normal cardiac function, and mutations in cMyBP-C cause cardiac muscle disease. The rod-shaped molecule is composed primarily of 11 immunoglobulin- or fibronectin-like domains, and is located at 9 sites, 43 nm apart, in each half of the A-band. To understand how cMyBP-C functions, it is important to know its structural organization in the sarcomere, as this will affect its ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
84
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(92 citation statements)
references
References 69 publications
(154 reference statements)
7
84
1
Order By: Relevance
“…1A) (4,5). The C-terminal domain (C10) is tightly bound to the thick filament backbone, and the N-terminal domains extend radially from the thick filament (6,7). Thus cMyBP-C's N-terminal domains are positioned to bind to neighboring actin filaments and/or the myosin S2 domain to modulate actomyosin activity.…”
mentioning
confidence: 99%
“…1A) (4,5). The C-terminal domain (C10) is tightly bound to the thick filament backbone, and the N-terminal domains extend radially from the thick filament (6,7). Thus cMyBP-C's N-terminal domains are positioned to bind to neighboring actin filaments and/or the myosin S2 domain to modulate actomyosin activity.…”
mentioning
confidence: 99%
“…To determine if the A31P mutation altered antibody recognition of epitopes in C0 we made use of a polyclonal antibody raised against full-length cMyBP-C that preferentially recognizes epitopes within the C0 domain (C-pro [23, 24]). Figure 2 shows western blots (WB) and Coomassie (C) stained gels loaded with increasing amounts of C0C2-WT and C0C2-A31P.…”
Section: Resultsmentioning
confidence: 99%
“…The sensitivity of the C-pro antibody to a single epitope is surprising because this polyclonal antibody was raised against full-length native cMyBP-C purified from rat heart [23] and is thus expected to react with numerous epitopes throughout the entire length of cMyBP-C. However, recent epitope mapping experiments revealed that the C-pro polyclonal antibody preferentially reacts with epitopes in C0 and to a lesser extent with other N-terminal domains of cMyBP-C such as the regulatory M-domain [24]. The significance of the strong antigenic nature of C0 is currently unknown, but the N-terminus of cMyBP-C has been identified in the development of immunogenic myocarditis suggesting that it is especially provocative to immune cells [30, 31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These phenotypes were not observed for the RLC mutants. One common denominator for both light chains could be the interaction between the ELC- and RLC-containing lever arm domain and actin via the cardiac MYBP-C, which was recently shown to span the neck domain of myosin head and actin with the C-terminal domains of cMyBP-C positioned along the thick filament surface, and the N-terminus of cMyBP-C extending toward neighboring thin filaments (Lee et al 2015). Interestingly, even though the ELC does not bind calcium, A57G-ELC and M173V-ELC both left shifted the calcium sensitivity of force (Table 1), a hallmark of HCM disease, suggesting the possibility of the N-terminus ELC mediated cross talk between the thick and thin filaments and resultant alterations in pCa 50 .…”
Section: Differences Between Rlc and Elc Phenotypesmentioning
confidence: 99%